Antimicrobial activity and cytotoxicity trait of a bioactive peptide purified from Lactococcus garvieae subsp. bovis BSN307T. (27th February 2021) - Varsha, K.K.; Nampoothiri, K.M.; Shilpa, G.; Priya, S.
Abstract: A bioactive peptide of 8595 Da was purified from the cell free supernatant of Lactococcus garvieae subsp. bovis BSN307 T . MALDI MS/MS peptide mapping and the data base search displayed no significant similarity to any reported antimicrobial peptide of LAB. This peptide at a dose concentration of 200 µg ml −1 inhibited the growth of both Gram‐positive and Gram‐negative bacteria by 58–89% and a dose of 500 µg ml −1 scavenged 50% of DPPH‐free radicals generated. Interestingly, cytotoxicity assay demonstrated that 17 µg ml −1 of peptide selectively inhibited 50% proliferation of mammalian cancer cell lines HeLa and MCF‐7 whereas normal H9c2 cells remained unaffected. Fluorescent microscopic analysis after DAPI nuclear staining of HeLa cells showed characteristics of apoptosis and activation of caspase‐3 was ascertained by caspase‐3 fluorescence assay. Abstract : Significance and Impact of the Study: Lactococcus garvieae subsp. bovis, a mammalian gut originated lactic acid bacterium produces a bioactive peptide, not reported before, that holds antimicrobial and cancer cell‐specific cytotoxicity. Antioxidant activity of the peptide as confirmed by free radical scavenging gives additional advantage to this strain and along with our earlier investigations, we conclude that the culture has the potential to be developed as a probiotic.